2019
DOI: 10.1111/adb.12833
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to ethanol sensitization predicts higher intake and motivation to self‐administer ethanol: Proof of the incentive salience sensitization theory?

Abstract: Ethanol-induced behavioral sensitization (EIBS) is thought to play a key role in addiction. However, whether EIBS is linked to an increase in the motivation to selfadministerethanol in an operant paradigm has never been demonstrated, and thus, the motivational sensitization theory (increase in drug wanting) has not been yet confirmed. We investigated using the operant ethanol self-administrationparadigm if the motivation to self-administerethanol (breakpoint) is increased in female mice prone to develop EIBS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Our data showed that, in contrast to findings with nicotine 43 and cocaine 44 , tDCS did not modulate the hedonic effect of ethanol assessed in the place preference paradigm, a test that combines Pavlovian conditioning and testing in a drug-free state. Furthermore, tDCS also did not modulate the expression of ethanol-induced behavioral sensitization, which has previously been linked to high ethanol intake in operant procedures 49 . In contrast, tDCS robustly reduced the reacquisition of ethanol consumption (50% decrease) following extinction in an operant paradigm.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our data showed that, in contrast to findings with nicotine 43 and cocaine 44 , tDCS did not modulate the hedonic effect of ethanol assessed in the place preference paradigm, a test that combines Pavlovian conditioning and testing in a drug-free state. Furthermore, tDCS also did not modulate the expression of ethanol-induced behavioral sensitization, which has previously been linked to high ethanol intake in operant procedures 49 . In contrast, tDCS robustly reduced the reacquisition of ethanol consumption (50% decrease) following extinction in an operant paradigm.…”
Section: Discussionmentioning
confidence: 67%
“…Behavioral sensitization is defined as a progressive and long-lasting increase in specific behaviors after repeated drug exposure, with the most studied behavior being locomotion. A recent study showed that in mice, sensitization to the motor stimulant effects of ethanol was associated with facilitation of the acquisition of ethanol self-administration in an operant task 49 . It was therefore of interest to evaluate the impact of tDCS on ethanol-induced behavioral sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The vast majority of studies on operant ethanol self-administration in rodents has been carried out in rats, and only very few studies have been published in mice. 29 Rats have been suggested to be the smart choice for studies on behavioral genetics and particularly in the addiction field. 30 We recently proposed a new procedure in outbred rats to mimic BD behavior, and we demonstrated that our model displays good face validity and predictive validity.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on voluntary BD in rodents are using the drinking‐in‐the‐dark model in inbred mice 28 . The vast majority of studies on operant ethanol self‐administration in rodents has been carried out in rats, and only very few studies have been published in mice 29 . Rats have been suggested to be the smart choice for studies on behavioral genetics and particularly in the addiction field 30 .…”
Section: Discussionmentioning
confidence: 99%